The product rule of logarithms states that \(\log_b M + \log_b N = \log_b (M \cdot N)\).
Substitute \(M = 9\) and \(N = 4\) into the product rule: \[ \log_7 9 + \log_7 4 = \log_7 (9 \cdot 4) \]
Calculate the product inside the logarithm: \[ \log_7 (9 \cdot 4) = \log_7 36 \]
\( \boxed{\log_7 36} \)
Oops, Image-based questions are not yet availableUse Solvely.ai for full features.
Failed. You've reached the daily limit for free usage.Please come back tomorrow or visit Solvely.ai for additional homework help.